1997
DOI: 10.1046/j.1365-2141.1997.2473063.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of liposomal versus conventional amphotericin B for the treatment of pyrexia of unknown origin in neutropenic patients

Abstract: Summary.One hundred and thirty-four adults and 204 children were randomized in two prospective, parallel comparative multicentre trials to receive either conventional amphotericin B 1 mg/kg/d (c-AMB), liposomal amphotericin B 1 mg/kg/d (L-AMB1) or liposomal amphotericin B 3 mg/ kg/d (L-AMB3). Patients were entered if they had a pyrexia of unknown origin (PUO) defined as temperature of 38ЊC or more, not responding to 96 h of systemic broad-spectrum antibiotic treatment, and neutropenia (< 0 . 5 × 10 9 /l). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
237
5
12

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(265 citation statements)
references
References 6 publications
9
237
5
12
Order By: Relevance
“…This practice is based upon the results of clinical trials that have demonstrated reductions of 50-75% in the incidence of ARF [13][14][15][16][17]. In these studies the development of ARF, usually defined as a 50% rise in the basal serum creatinine levels and a peak creatinine level higher than 2.0 mg/dL, occurred in 34% to 49% of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This practice is based upon the results of clinical trials that have demonstrated reductions of 50-75% in the incidence of ARF [13][14][15][16][17]. In these studies the development of ARF, usually defined as a 50% rise in the basal serum creatinine levels and a peak creatinine level higher than 2.0 mg/dL, occurred in 34% to 49% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of clinical trials, liposomal amphotericin has been recommended for the prevention of acute renal failure (ARF) [13][14][15][16][17]. These studies included a largely unselected population of patients, with many of them being treated at intensive care units, using vasoactive drugs, and with multiple risk factors for developing ARF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This lipid formulation has a favorable toxicity profile when compared to conventional amphotericin B deoxycholate [2][3][4] and has been approved for use at dosages ranging from 3 to 6 mg/kg/day for indications including empirical therapy of persistent febrile neutropenia, systemic aspergillus, candida, and cryptococcus infections, visceral leishmaniasis, and cryptococcal meningitis in HIV infected patients. The improved safety and tolerability of this formulation have allowed for the use of increasingly higher dosages for the treatment of refractory infections [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…17 In a further randomized study, liposomal amphotericin B in the empirical setting of fever of unknown origin was shown to be effective even at a dose level of l mg/kg body weight. 18 Furthermore, the dosage of liposomal amphotericin B can be increased safely to dosages higher than 3 mg/kg if necessary. 19 To investigate the impact of PCR as a diagnostic tool for guiding preemptive antifungal therapy, we compared the incidence of IFIs as well as the overall and IFI-related mortality in patients after Allo-SCT randomized to PCRbased preemptive as opposed to empirical treatment with liposomal amphotericin B.…”
Section: Introductionmentioning
confidence: 99%